Effects of a microplastic mixture differ across trophic levels and taxa in a freshwater food web: In situ mesocosm experiment - Yıldız, Dilvin; Yalçın, Gülce; Jovanović, Boris; Boukal, David S; Vebrová, Lucie; Riha, Derya; Stanković, Jelena; Savić-Zdraković, Dimitrija; Metin, Melisa; Akyürek, Yasmin Naz; Balkanlı, Deniz; Filiz, Nur; et al. (The Science of the total environment, 2022)
The ubiquitous presence of microplastics (MP) in aquatic ecosystems can affect organisms and communities in multiple ways. While MP research on aquatic organisms has primarily focused on marine ecosystems and laboratory experiments, the community-level effects of MP in freshwaters, especially in lakes, are poorly understood. To examine the impact of MP on freshwater lake ecosystems, we conducted the first in situ community-level mesocosm experiment testing the effects of MP on a model food web with zooplankton as main herbivores, odonate larvae as predators, and chironomid larvae as detritivores for seven weeks. The mesocosms were exposed to a mixture of the most abundant MP polymers found in freshwaters, added at two different concentrations in a single pulse to the water surface, water column and sediment. Water column MP concentrations declined sharply during the first two weeks of the experiment. Contrary to expectations, MP ingestion by zooplankton was low and limited mainly to large-bodied Daphnia, causing a decrease in biomass. Biomass of the other zooplankton taxa did not decrease. Presence of MP in the faecal pellets of odonate larvae that fed on zooplankton was indicative of a trophic transfer of MP. The results demonstrated that MP ingestion varies predictably with MP size, as well as body size and feeding preference of the organism, which can be used to predict the rates of transfer and further effects of MP on freshwater food webs. For chironomids, MP had only a low, short-term impact on emergence patterns while their wing morphology was significantly changed. Overall, the impact of MP exposure on the experimental food web and cross-ecosystem biomass transfer was lower than expected, but the experiment provided the first in situ observation of MP transfer to terrestrial ecosystems by emerging chironomids.
Keywords: Animals; Plastics; Food Chain; chemické látky znečišťující vodu; Water Pollutants, Chemical; Microplastics; jezera; Lake ecosystem; Odonata; Zooplankton; mikroplasty; Microplastic; plastické hmoty; voda; Water; Chironomidae; Trophic transfer; ekosystém; Ecosystem; Lakes; zvířata; zooplankton; potravní řetězec